Existence of Positive Solutions for Multipoint Boundary Value Problem with p-Laplacian on Time Scales. (9th June 2009) - Zhang, Meng; Sun, Shurong; Han, Zhenlai
Abstract : We consider the existence of positive solutions for a class of second-order multi-point boundary value problem withp -Laplacian on time scales. By using the well-known Krasnosel'ski's fixed-point theorem, some new existence criteria for positive solutions of the boundary value problem are presented. As an application, an example is given to illustrate the main results.